India and ASEAN : non-traditional security threats - Raghavan, V. R.; Raghavan, V. R.; Centre for Security Analysis (Chennai, India); Hanns-Seidel-Stiftung. (Chennai : EastWest Books (Madras), 2007)
Papers presented to a seminar held in 2005 in Madras, India; organized by Centre for Security Analysis, and Hanns Seidel Foundation.
Keywords: ASEAN -- Influence -- Congresses; Environmental protection -- Southeast Asia -- Congresses; India -- Relations -- Southeast Asia -- Congresses; Southeast Asia -- Relations -- India -- Congresses; India -- Politics and government -- 1977- -- Congresses; Southeast Asia -- Politics and government -- 1945- -- Congresses